2001
DOI: 10.1002/cne.1343
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic relationships between aromatase and androgen receptor mRNA expression in the hypothalamus and amygdala of adult male cynomolgus monkeys

Abstract: This study mapped the regional locations of cells expressing cytochrome P450 aromatase (P450AROM) and androgen receptor (AR) mRNAs in the adult male macaque hypothalamus and amygdala by in situ hybridization histochemistry using monkey-specific cRNA probes. High densities of P450AROM and AR mRNA-containing neurons were observed in discrete hypothalamic areas involved in the regulation of gonadotropin secretion and reproductive behavior. P450AROM mRNA-containing neurons were most abundant in the medial preoptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 103 publications
(107 reference statements)
2
56
1
1
Order By: Relevance
“…These effects of T may be mediated in part through the amygdala, which is highly responsive to threat signals [25,26] and contains androgen receptors [69,70]. In fact, preliminary evidence from fMRI studies conducted in our laboratory (unpublished data) and by others [71] suggest a relationship between T and amygdala responsiveness to anger faces.…”
Section: Discussionmentioning
confidence: 66%
“…These effects of T may be mediated in part through the amygdala, which is highly responsive to threat signals [25,26] and contains androgen receptors [69,70]. In fact, preliminary evidence from fMRI studies conducted in our laboratory (unpublished data) and by others [71] suggest a relationship between T and amygdala responsiveness to anger faces.…”
Section: Discussionmentioning
confidence: 66%
“…Data have been reported showing a positive role for androgens in aromatase expression in rat testicular somatic cells; these studies were in the presence of a saturating amount of testosterone (200 ng/ml) (Levallet & Carreau 1997, Genissel & Carreau 2001. Moreover in the rat brain (Roselli & Resko 1984) as well as in the brain of male rhesus monkeys (Resko et al 2000) androgens regulate aromatase at both the transcriptional level and the enzyme activity via the presence of ARs (Roselli et al 2001). In male gonad the localization of AR is a subject of controversy (for review see Eddy 2002); some reports have demonstrated the presence of immunoreactive AR in germ cells (Vornberger et al 1994, Zhou et al 1996 and other studies have shown that only testicular somatic cells express AR (Suarez-Quian et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, pharmacological challenge studies indicate that a single dose of [11,12]; (2) these subcortical brain structures are rich in both androgen and estrogen receptors [30,31,32]; and (3) these regions play a key role in potentiating reactive aggression in animals [33]. Studies outside the scanner have also yielded interesting effects of testosterone on social cognition and behavior.…”
Section: Pharmacological Challenge Studiesmentioning
confidence: 99%